PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH BRI DI KABUPATEN BULELENG - Dewantari, Fiorentina; Telagawathi, Ni Luh Wayan Sayang; Widiastini, Ni Made Ary (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Bank Rakyat Indonesia (BRI) has an important role in the Indonesian economy. Currently, BRI’s role is not only limited to providing conventional financial services, but also has a role in supporting financial inclusion, microeconomic growth, agricultural sector development, and community empowerment. BRI provides various service and transaction innovations to maintain customer loyalty. This research aims to examine the role of customer satisfaction in mediating service quality and trust in BRI customer loyalty in Buleleng Regency. The sample for this research was 80 BRI customers in the Buleleng area. The analysis used is path analysis. The independent variables are service quality, trust and customer satisfaction, while the dependent variable is customer loyalty. The results of this research show that service quality on customer loyalty through customer satisfaction shows a significant influence. For customer trust in customer loyalty through customer satisfaction, the results did not have a significant effect.